City Mazes Around the World Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
From New York City to Tokyo and Berlin to Sydney, the streets of the 15 cities included in this book are filled with a fascinating showcase of local landmarks and awesome attractions. How will you get from the Brooklyn Bridge to Central Park in New York City? Or find your way to Topkapi Palace in Istanbul? Each spread
Keywords: dept.lib

Mr. Bear's Birthday Translated by Wendeline Hardenberg - Aracil, Virginie (Twirl Books, 2020)
Mr. Bear is having a birthday party, and everyone is welcome! It doesn’t matter if you’re big, small, don’t have teeth, or are afraid of the dark . . . you’re invited! In this wonderfully illustrated oversize book that celebrates inclusion as well as a special day, Mr. Bear’s Birthday also includes lots of gifts—with f
Keywords: dept.lib

Who Does What? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Who gathers honey? Who designs clothes? Who makes lunch for students?  So many jobs can be found in this delightful and satisfying sliding panel format for preschoolers. The 36 panels feature jobs in various settings: in the orchestra, at the market, at school, and more! Each new spread offers clues to the right respon
Keywords: dept.lib

The Ultimate Book of Horses Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl Books, 2020)
Horses are amazing creatures! The Ultimate Book of Horses provides hours of hands-on discovery and includes age-appropriate information on the …
Keywords: dept.lib

Miki Takes a Bath Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Splish-splash! Miki’s taking a bath! Bathtime couldn’t be more fun with Miki showing how it’s done in this delightful pop-up …
Keywords: dept.lib

Animals at Night Translated by Wendeline Hardenberg - Hedelin, Pascale (Twirl Books, 2020)
The fluffy feathers of an owl, the bumpy skin of a toad, and the thick fur of a river otter—there’s …
Keywords: dept.lib

Trains Translated by Wendeline Hardenberg - Prénat, Sophie (Twirl Books, 2020)
All aboard! Chock-full of fascinating facts, Ultimate SpotlightTM Trains offers young readers a closer look into the marvelous world of …
Keywords: dept.lib

Mr. Lion Dresses Up! Translated by Wendeline Hardenberg - Teckentrup, Britta (Twirl Books, 2020)
How exciting! Mr. Lion has been invited to a party! But what will he wear? A handsome suit . . …
Keywords: dept.lib

Whose Baby is This? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Keywords: dept.lib

Patience Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Waiting is not easy, whether it’s waiting to play with a toy or to eat a snack. And Little Kangaroo, Little Cat, and their friends are just not sure that they can be patient. But as their grown-ups show them, being patient doesn’t have to be boring or unbearable. There are many fun things they can do while they wait! C
Keywords: dept.lib

Magnetology: Vehicles Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl Books, 2020)
Take a ride—whether it’s on a boat, plane, or on a rocket ship! Kids can use the 45 magnetic pieces included to fill 5 oversized scenes in this Magnetology™ title. The all-in-one play set features fascinating information, just right for its audience, about all types of vehicles: those that travel on the road, on a farm
Keywords: dept.lib

Brothers and Sisters Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Little Crocodile, Little Monkey, and all their friends have siblings—siblings who take their things, make a mess, or just get …
Keywords: dept.lib